ANTHROPOMETRIC STUDY OF STUDENTS PRACTICING PHYSICAL ACTIVITIES IN A PRIVATE SCHOOL, RIO DE JANEIRO (Fiep Bulletin - online, 2014)
Adolescence is the period of life characaterized by deep transformations in the human body. The widely used method to evaluate bodily changes is anthropometry, in the context of kineanthropometry. This study aims at delineating the anthropometric profile of students who practice physical activities in a private school in the city of Rio de Janeiro, in the state of Rio de Janeiro. It is a descriptive cross-cut study of primary base carried out among teenagers enrooled in the 5th and 6th grade of elementary school, from 10 to 14 years old in August 2006. The statistic package SPSS version 10.0 was applied for the analysis. Among 50 teenagers 62% were girls at the average age of 11.50.8 years, and the boys, 11.60.8 years. The analsyis of the nutritional state measured by the percentile BMI (Bodily mass Index) revealed that there was higher prevalence of overweight among the boys (47.4%). High prevalence of overweight was detected among the girls for overweight (41.9%) and low weight (12.9%). The conclusion was that both male and female teenagers feature high prevalence of overweight, mainly at the age from 10 to 12 years.
Keywords: Teenagers; Anthropometry; Physical Activity